The colours and contours of compassion: A systematic review of the perspectives of compassion among ethnically diverse patients and healthcare providers. - Pavneet Singh; Kathryn King-Shier; Shane Sinclair (PLoS ONE, 2018)
Objective To identify and describe the perspectives, experiences, importance, and impact of compassionate care among ethnically diverse population groups. Methods A systematic search of peer-reviewed research focused on compassionate care in ethnically diverse populations published between 1946 and 2017 was conducted. Results A total of 2296 abstracts were retrieved, out of which 23 articles met the inclusion criteria. Synthesis of the literature identified the perspectives, facilitators and barriers of compassion in healthcare within ethnic groups. Compassion was described as being comprised of healthcare provider (HCP) virtues (honesty, kindness, helpful, non-judgment) and actions (smile, touch, care, support, flexibility) aimed at relieving the suffering of patients. The importance and impact of providing compassion to ethnically diverse patients was also identified which included overcoming cultural differences, alleviating distress at end-of-life, promoting patient dignity and improving patient care. This review also identified the need for more contextual studies directly exploring the topic of compassion from the perspectives of individuals within diverse ethnic groups, rather than superimposing a pre-defined, enculturated and researcher-based definition of compassion. Conclusions This review synthesizes the current evidence related to perceptions of compassion in healthcare among diverse ethnic groups and the role that compassion can play in bridging ethno-cultural differences and associated challenges, along with identifying gaps in literature related to compassionate care within diverse ethnic groups. Establishing an evidence base grounded in the direct accounts of members of diverse ethnic communities can enhance culturally sensitive compassionate care and improve compassion related health outcomes among diverse ethnic groups.